Effects of self-affirmation on responses toward graphic cigarette warning labels: testing the mediating role of perceived susceptibility and self-efficacy. Issue 1 (12th November 2020) - Ma, Zexin; Nan, Xiaoli; Iles, Irina A.; Butler, James; Feldman, Robert; Wang, Min Qi
Abstract : Purpose: The purpose of this study is to examine the effects of self-affirmation on African American smokers' intentions to quit smoking sooner and desire to stop smoking altogether in response to viewing graphic cigarette warning labels. It also tested the mediating role of perceived susceptibility and self-efficacy in explaining the impact of self-affirmation. Design/methodology/approach: African American smokers ( N  = 158) were recruited to participate in a controlled experiment. Participants first completed a short questionnaire about their demographic background and smoking-related attitudes and behavior. They were then randomly assigned to engage in either a self-affirmation task or a control task and viewed two graphic cigarette warning labels subsequently. Participants then responded to a questionnaire about their perceived susceptibility to smoking-related diseases, perceived self-efficacy to quit smoking, intentions to quit smoking and desire to stop smoking altogether. Findings: Results showed that engaging in self-affirmation prior to exposure to graphic cigarette warning labels increased African American smokers' perceived susceptibility to smoking-related diseases, but decreased their perceived self-efficacy to quit smoking. Furthermore, self-affirmation indirectly enhanced smokers' intentions to quit smoking sooner and desire to stop smoking altogether through increased perceived susceptibility. It also had an unexpected negative indirect effect on intentions to quit smoking sooner through decreased self-efficacy. Originality/value: This study is one of the few studies that investigates the effect of self-affirmation on African American smokers' responses toward graphic cigarette warning labels.